STRATEGI PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI RSUD BERKAH KABUPATEN PANDEGLANG BANTEN - Ende, Ende; Aulia, Risma (SINERGI : Jurnal Riset Ilmiah, 2024)
Productivity is something that always wants to be improved because it can describe the level of efficiency and effectiveness of employee work. The purpose of this study is to determine the level of employee work productivity, factors that have an impact on employee work productivity and formulate strategies to improve employee work productivity at Berkah Hospital, Pandeglang Banten Regency. The type of research used in this study is qualitative research with a descriptive approach. Data collection techniques in this research are interviews, observation, documentation, literature. Informants in this study were employees who worked at the Blessing Hospital of Pandeglang Banten Regency. The informants were two people, namely the Head of the Payment Counter Room and the Ambulance Driver. The result of this research is the work productivity of employees at the Blessing Hospital of Pandeglang Banten Regency is fairly good, but there are several issues that are of concern to the leaders or directors of the hospital. The level of employee work productivity at the Berkah Hospital of Pandeglang Banten requires improvement efforts through employee motivation, training, discipline, skills or competence, technological sophistication, social security, and rewards.